Tournament solutions - Brandt, F; Brill, M; Harrenstein, B (Cambridge University Press, 2016)
This handbook, written by thirty-six prominent members of the computational social choice community, covers the field comprehensively. Chapters devoted to each of the field's major themes offer detailed introductions.